Which expression is equivalent to (3x-6)(4x+1)
1 answer:
Answer:
12x^2 -21x -6
Step-by-step explanation:
(3x-6)(4x+1)
FOIL
first 3x*4x= 12x^2
outer 3x*1 = 3x
inner -6*4x = -24x
last -6*1 = -6
Add them together
12x^2 +3x -24x -6
Combine like terms
12x^2 -21x -6
You might be interested in
Answer:
<h2> 75 is 3, groups </h2>
Step-by-step explanation:
Try counting by qurter
Answer:
P=-2.3662299854
Step-by-step explanation:
6.87p = - 7.056 -9.2
So 6.87p= - 16.256
P=-2.3662299854
73.61 is the answer... you just subtract the numbers
1/3=0.33 repeatingly
3/8=0.375
2/5=0.4
1/2=0.5
3/8 is greater.
Step-by-step explanation:
it has only 1 root
<h2>Mark me brainliest</h2>